Uterine perforation during intrauterine procedures and its management - Driák, Daniel; Sehnal, Borek; Jarošová, Lucie; Dvořáčková, Karolína (Ceska gynekologie, 2022)
OBJECTIVE: Uterine perforation is a potential, not rare complication of all intrauterine procedures and may be associated with injury of surrounding organs and structures. The incidence, risk factors, possible prevention, dia-gnosis, management and impact on future reproduction is reviewed here. METHODS: Systematic review of available sources on the topic was carried out using the PubMed database and textbooks of Czech authors. CONCLUSION: Some risk factors that make access to the uterine cavity difficult may be prevented, however, others remain unpreventable. For patients in whom the perforation occurred during sondage, dilatation or insertion of blunt and cold instrument, without significant bleeding and who are hemodynamically stable, observation is recommended rather than immediate abdominal exploration. The exception are young women planning pregnancy in whom endoscopic suture is indicated. Abdominal exploration is required in patients who have been injured by electrosurgical or sharp device, laser, vacuum curette, who are hemodynamically unstable or show signs of severe bleeding or visceral injury.
Keywords: Uterine Perforation; uterine perforation; risk factors; hysteroscopy; těhotenství; endometrial cancer; Uterus; uterus; dilatation and curettage; injury; ženské pohlaví; intrauterine device; Humans; perforace dělohy; Pregnancy; doppler ultrasound of uterine artery; pregnancy termination; Female; lidé